Safety and efficacy of a feed additive consisting of Bacillus subtilis DSM 32324, Bacillus subtilis DSM 32325 and Bacillus amyloliquefaciens DSM 25840 (GalliPro® Fit & GalliPro® Fit 10) for all poultry (Chr. Hansen A/S) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Roberto Edoardo Villa; Giovanna Azimonti; Eleftherios Bonos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Ronette Gehring; Boet Glandorf; Maryline Kouba; Marta López‐Alonso; Francesca Marcon; et al. (EFSA Journal, 2025)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the safety and efficacy of a feed additive consisting of Bacillus subtilis DSM 32324, B. subtilis DSM 32325 and Bacillus amyloliquefaciens DSM 25840 (GalliPro® Fit 10) as a zootechnical feed additive for all poultry species. The additive in a less concentrated form (GalliPro® Fit) is already authorised for use in feed and water for drinking for poultry for fattening, reared for laying or reared for breeding. With the current application, the applicant is seeking the authorisation for use in feed and water for drinking for all poultry. In addition, the applicant is seeking the modification of the terms of the existing authorisation by introducing a new formulation with a 10‐fold increased concentration of the active agents in the additive (from 3.2 × 109 to 3.2 × 1010 colony forming units (CFU)/g additive). The FEEDAP Panel concluded that the additive is considered safe for the target species, including poultry species for laying and breeding, consumers and the environment at the proposed conditions of use. Both forms of the additive are non‐irritant to the eyes but are considered skin and respiratory sensitisers, and any exposure through skin and respiratory tract is considered a risk. The additive has the potential to be efficacious as a zootechnical additive in all poultry at 1.6 × 109 CFU/kg feed and 5.4 × 108 CFU/L water for drinking.